Mbah Kholil Bangkalan: Titik Simpul Relasi Ulama Madura, Nusantara dan Haramain - Muniri Muniri (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Mbah Kholil Bangkalan is a phenomenal Kyai, he was having role to educate his studens to be knowledgeable, insightful, firmness and integrity, both of religion and nation. His wisdom is combined with ability to give ijazah of inner strength to resist Dutch colonialism. All The Kyai at that time, were making ijma' sukuti (silent agreement), for santri who want to continue their study to Mecca and hwo want to build islamic boarding school, they have to have blessing from Mbah Kholil Bangkalan. Based on ijma’ sukuti, he was called Kyai Labang. Almost the Kyai phenomenal in Java-Madura, even up to foreign countries quite a lot of geneologis related to the scientist with Mbah Kholil Bangkalan. The genealogical relationship of the scientists will be requied by studying or ever